A comparison of clinical parameters at presentation, pathological outcomes and biochemical relapse between NHS and private patients undergoing radical prostatectomy at a single centre in the United Kingdom. (September 2016) - Robinson, Simon; Laniado, Marc; Farooq, Assad; Motiwala, Hanif; Omar, Mohamed; Summers, Dominic; Rao, Amrith; Ali, Mufeed; Meiers, Isabelle; Karim, Omer
Objective: We studied our hypothesis that patients with private health insurance (PHI) with prostate cancer present with more favourable pathological outcomes. Patients and methods: Data were analysed from 554 patients undergoing radical prostatectomy from 2002 to 2010. A total of 328 patients under the NHS and 226 men had PHI. Two groups were compared for age, PSA, Gleason score, number of cores involved, maximum tumour length on biopsy core, socioeconomic status, imaging and pathological outcomes. Results: PHI presented at a younger age (63 vs 61, p = 0.008) and lower mean PSA (9.5 vs 8.04, p = 0.0005). Staging MRI showed a significant difference in usage (77% vs 45% p < 0.001). Importantly there was significant difference in the total tumour volume (4 cc vs 8 cc, p = 0.001). There were significantly more wealthy patients being seen privately ( p < 0.0001). However, on the final Cox regression model only grade, stage and insurance status were significant predictors of BCR. Conclusions: Patients with PHI were younger, had a lower presenting PSA and were wealthier. There is a significant difference in the social profile seen, but wealth itself is not protective yet health insurance is. Insurance status and not social status represents a factor in predicting final pathological outcomes after RRP.